Targeting Causes of Burnout in Residency: An Innovative Approach Used at Hennepin Healthcare. (25th January 2021) - Quirk, Rosemary; Rodin, Holly; Linzer, Mark
Abstract : Supplemental Digital Content is available in the text. Abstract : Problem: Rates of burnout are high in physicians in the United States. While others have reported on the success of burnout-reduction strategies on practicing physicians and residents, few strategies have approached the problem longitudinally in residents. Approach: From 2014 to 2019, the authors used a previously developed survey to assess factors related to resident burnout, including sleep, personal time, professional fulfillment, effects on relationships, program recognition, and peer support. At Hennepin Healthcare, a safety-net hospital in Minneapolis, Minnesota, the authors created a reproducible process for collecting data from internal medicine residents annually, and for using evidence-based conceptual frameworks to develop a continuous improvement method to address worklife across training years. Interventions included jeopardy coverage for essential life events, a newsletter celebrating resident achievements, removal of after-hours consult pager call, an extra day off for senior residents on the wards, and care packages distributed to night teams. Outcomes: Annually from 2014 to 2019, 40/66 (60.6%) to 62/73 residents (84.9%) completed the survey (average response rate was 72.1% over 6 years). Survey results were shared with residents in multiple formats, and feedback was requested, demonstrating that burnout reduction is a priority for program leadership. High professional fulfillment scores were documented every year. Self-reported rates of burnout were between 25% and 35%. Significant improvements were seen in perception of empathy, sleep impairment, and peer support. Next Steps: The authors developed a plan for minimizing burnout, which includes the following evidence-based domains: workload, control, balance in effort and reward, work–life balance, fairness, values, support, gender equity, moral distress, and moral injury. Additional interventions include protected time for didactics, trauma-informed care training, and addressing workplace racism. The authors aspire to achieve an integrated culture of well-being for residents and faculty; foster an efficient, effective, and fair learning environment; and reduce—and ultimately eliminate—burnout.